Transglutaminase 2 Inhibition Reverses Mesenchymal Transdifferentiation of Glioma Stem Cells by Regulating C/EBPβ Signaling - Jinlong Yin; Young Taek Oh; Jeong-Yub Kim; Sung Soo Kim; Eunji Choi; Tae Hoon Kim; Jun Hee Hong; Nakho Chang; Hee Jin Cho; K. Jason; Jeong Cheol Kim; Hyung Joon Kwon; et al. (2017)
Necrosis is a hallmark of glioblastoma (GBM) and is responsible for poor prognosis and resistance to conventional therapies. However, the molecular mechanisms underlying necrotic microenvironment-induced malignancy of GBM have not been elucidated. Here, we report that transglutaminase 2 (TGM2) is upregulated in the perinecrotic region of GBM and triggered mesenchymal (MES) transdifferentiation of glioma stem cells (GSC) by regulating master transcription factors (TF), such as C/EBPβ, TAZ, and STAT3. TGM2 expression was induced by macrophages/microglia-derived cytokines via NF-κB activation and further degraded DNA damage-inducible transcript 3 (GADD153) to induce C/EBPβ expression, resulting in expression of the MES transcriptome. Downregulation of TGM2 decreased sphere-forming ability, tumor size, and radioresistance and survival in a xenograft mouse model through a loss of the MES signature. A TGM2-specific inhibitor GK921 blocked MES transdifferentiation and showed significant therapeutic efficacy in mouse models of GSC. Moreover, TGM2 expression was significantly increased in recurrent MES patients and inversely correlated with patient prognosis. Collectively, our results indicate that TGM2 is a key molecular switch of necrosis-induced MES transdifferentiation and an important therapeutic target for MES GBM. Cancer Res; 77(18); 4973-84. ©2017 AACR.